2016
DOI: 10.11648/j.ijber.20160506.17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Entrepreneurship Education on Students Orientation Towards Entrepreneurship at the Malawi Polytechnic

Abstract: Entrepreneurship education has proliferated in universities following empirical studies linking it to entrepreneurship practice. The University of Malawi introduced entrepreneurship and innovation course to the bachelor of business administration programme and aims to make entrepreneurship a core module across academic programmes. This study assessed the effects of the entrepreneurship and innovation course on the entrepreneurial orientation of students thereby joining research into the investigation of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
2
10
0
1
Order By: Relevance
“…Hence, there is a positive and significant relationship between entrepreneurship education and student attitude. Likewise, the results obtained in the research is similar to research by Mwatsika and Sankhulani (2016) entrepreneurship education creates positives waves that create positive student attitude. Hence, a positive mind and positive would incline graduates to engage in entrepreneurial activity.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Hence, there is a positive and significant relationship between entrepreneurship education and student attitude. Likewise, the results obtained in the research is similar to research by Mwatsika and Sankhulani (2016) entrepreneurship education creates positives waves that create positive student attitude. Hence, a positive mind and positive would incline graduates to engage in entrepreneurial activity.…”
Section: Resultssupporting
confidence: 83%
“…Entrepreneurship education prepares students with entrepreneurial tools such as attitude, competencies, and skills (Abiah et al, 2017). Past research found that there is a correlation between entrepreneurship education and individual attitude toward entrepreneurship (Mwatsika and Sankhulani, 2016). Hence, attitude plays an important role in increasing entrepreneurial intention (Potishuk and Kratzer, 2017).…”
Section: The Relationship Between Entrepreneurship Education and Attimentioning
confidence: 97%
“…Students lack exposure to the entrepreneurial world and receive an ineffective entrepreneurship education from their family or during college. A student's entrepreneurial intentions can be stifled without exposure and experience, or with only a moderate level of entrepreneurial behavior (Mwatsika, C., and Sankhulani, E. 2016;).…”
Section: Objective 1: Measuring the Level Of Entrepreneurial Behaviormentioning
confidence: 99%
“…By 2020, the world's economic situation is expected to be more competitive due to the effects of globalization, such as free trade, advancement in technology and information, and diverse new opportunities that contribute to the destabilization of the business sector (Mwatsika and Sankhulani, 2016). _____________________________ Numerous studies have found that the entrepreneurial sector is an important alternative driver of a nation's economy that directly increases job opportunities (Mohamad, Abdullah, and Bakar, 2015;Nafukho and Muyia, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation